The impact of mind-clearing method in teaching reading book to second class intermediate students - Lect. Dr. Khamael Shakir Ghanim, Asst. Prof. Rafid Sabah Abdul Redha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims at knowing the impact of the mind-clearing method in teaching second year intermediate students “reading book”. To achieve the study objective, the researchers intentionally chose Arjwan middle school, located in Baghdad Directorate of Education Al-Rusafa/2, which includes five classes for the second intermediate class. Division (A) was chosen randomly to represent the experimental group, which is taught in the mind-clearing method, while Division (B) represented the control group, which is taught in the traditional way. The sample of the research included (79) female students divided into (39) students in the experimental group, and (40) female students in the control group.To achieve the objective of the research, the researchers put the following null hypothesis:There is no statistically significant difference between the average scores of the experimental group students who study (reading) according to the mind-clearing method, and the average scores of the control group students who study (reading) according to the traditional method. The researchers rewarded the students of the two research groups in the following variables: chronological age calculated in months, Arabic language subject grades for the previous year (2016/2017), and parents’ academic achievement. The researchers employed the t-test for two independent samples (t-test) to find out the significance of the difference at the level (0.05) between the two research groups according to the traditional method.